Environmental factors and symptoms in infants at high risk of allergy. Issue 2 (June 1989) - Burr, M L; Miskelly, F G; Butland, B K; Merrett, T G; Vaughan-Williams, E
Abstract : STUDY OBJECTIVE: To identify environmental determinants of six symptoms associated with allergic disease in infancy. DESIGN: Infants were participants in a prospective randomised controlled trial of feeding practices in families with a history of atopy. SETTING: Infants were recruited in two maternity hospitals in S Wales and followed up in the community for 1 year. PARTICIPANTS: Mothers of 519 infants agreed to participate, but 36 were excluded (mainly for moving home or failing to attend for follow-up), leaving 483 in the study (253 male, 230 female). Infants were followed up and examined for evidence of allergic disease at 3, 6, and 12 months. MEASUREMENTS AND MAIN RESULTS: At each examination, mothers were questioned about episodes of illness in the infant, and the data presented relate to (reported and observed) eczema and nasal discharge, and (reported) wheeze, prolonged colds, diarrhoea and vomiting. Mothers kept a diary with details of feeding for the first 6 months. All homes were visited by a nurse who took samples of dust for dust mite antigen analysis. Extensive socio-demographic data were collected. None of the factors studied showed a convincing relationship with eczema. In a multiple logistic regression analysis breast feeding appeared to protect against wheeze, nasal discharge, colds, vomiting and diarrhoea. Having more siblings increased the likelihood of prolonged colds, and (together with overcrowding) of wheeze and nasal discharge. Maternal smoking and low social class were associated with wheeze, and house dust antigen with prolonged colds. Respiratory symptoms were associated with some aspects of housing but these could not be distinguished clearly from other social factors. Babies born in Autumn were at increased risk of wheeze, vomiting and diarrhoea. CONCLUSIONS: Environmental factors play an important part in determining risk of symptoms in potentially atopic babies. These factors are in principle open to manipulation.